2010
DOI: 10.1203/00006450-201011001-00215
|View full text |Cite
|
Sign up to set email alerts
|

215 Cardiac Output Monitoring: Experimental Study in An Infant Shock Animal Model Comparing Pulmonary Arterial Thermodilution, Femoral Arterial Thermodilution and Bioreactance

Abstract: Background: Timing to indicate pharmacological PDA closure is controversial and varies widely among NICUs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Relevant studies show that Prox1 expression is related to tumor stage and grade, suggesting that Prox1 participates in the proliferation process of lung cancer cells [ 19 , 20 ]. Therefore, the MTT method was used to detect A549 and H446 cells’ growth overexpressing Prox1 after plasmid transfection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant studies show that Prox1 expression is related to tumor stage and grade, suggesting that Prox1 participates in the proliferation process of lung cancer cells [ 19 , 20 ]. Therefore, the MTT method was used to detect A549 and H446 cells’ growth overexpressing Prox1 after plasmid transfection.…”
Section: Resultsmentioning
confidence: 99%
“…It’s been suggested, that Prox1 is a downstream target gene of β-catenin/TCF in colon cancer, and Prox1 can lead to enhanced cell adhesion [ 30 ]. Others have confirmed that deletion, mutation, and hyper-methylation of the Prox1 gene can lead to the occurrence of biliary tumors, esophagus cancer, and breast cancer [ 20 , 31 ]. Previous experiments have proved that Rho protein can not only directly affect the construction of cytoskeleton but also participate in gene transcription regulation [ 32 ], thus indirectly affecting cytoskeleton and movement.…”
Section: Discussionmentioning
confidence: 99%